2019
DOI: 10.1302/0301-620x.101b7.bjj-2018-1309.r1
|View full text |Cite
|
Sign up to set email alerts
|

Pain catastrophizing, anxiety, and depression in hip pathology

Abstract: Aims Psychological factors play a critical role in patient presentation, satisfaction, and outcomes. Pain catastrophizing, anxiety, and depression are important to consider, as they are associated with poorer outcomes and are potentially modifiable. The aim of this study was to assess the level of pain catastrophizing, anxiety, and depression in patients with a range of hip pathology and to evaluate their relationship with patient-reported psychosocial and functional outcome measures. Patients and Methods Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(74 citation statements)
references
References 58 publications
5
66
1
2
Order By: Relevance
“…A secondary aim was to assess whether other radiographic and clinical variables were also related to age of onset in DDH and FAIS. It has been shown that elevated levels of pain catastrophizing, anxiety and depression are significantly present in those with DDH and FAIS [34]. Given the ability to negatively modulate an individual’s perception of pain and worsen outcome, it was predicted that a higher PCS score and HADS score would lead to a younger age of onset in FAI syndrome and DDH.…”
Section: Discussionmentioning
confidence: 99%
“…A secondary aim was to assess whether other radiographic and clinical variables were also related to age of onset in DDH and FAIS. It has been shown that elevated levels of pain catastrophizing, anxiety and depression are significantly present in those with DDH and FAIS [34]. Given the ability to negatively modulate an individual’s perception of pain and worsen outcome, it was predicted that a higher PCS score and HADS score would lead to a younger age of onset in FAI syndrome and DDH.…”
Section: Discussionmentioning
confidence: 99%
“…Hip pain and dysfunction may play a signi cant role in a patient's psychological well-being. 11 We further con rmed this link between function and psychology; speci cally, a link between improved activity of daily living function and improved psychological factors.…”
Section: Discussionmentioning
confidence: 54%
“…2, 3, 7-9, 11, 36 Additionally, it has been previously shown that this relationship is quanti able, as higher reported subjective functioning in hip patients is associated with lower levels of pain catastrophizing, anxiety, and depression at time of presentation. 11,35 In our cohort, pain catastrophizing scores were particularly elevated in patients with lower function scores, as di culties with activities of daily living, and the resulting loss of self-su ciency, lend themselves to pain catastrophizing. 8,37 After assessing the psychological pro le of our cohort prior to treatment, we next determined how each measured psychological category changed following treatment.…”
Section: Discussionmentioning
confidence: 67%
“…Recently, a notable concept related to depression is pain catastrophizing [ 14 , 15 , 16 ], defined as sustained negative thoughts resulting from an excessive fear of pain and consisting of three subfactors: rumination, magnification, and helplessness [ 17 , 18 ]. Furthermore, pain catastrophizing was found to be a prediction factor not only for depression but also for chronic pain interference [ 12 ].…”
Section: Introductionmentioning
confidence: 99%